1989
DOI: 10.1111/j.1365-2494.1989.tb01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation studies in the development of a commercial bacterial inoculant as an additive for grass silage

Abstract: Two 2x3 factorial design experiments were conducted during 1985 to compare the effect of treating grass at ensiling with a silage inoculant (Imperial Chemical Industries pic) or formic acid with an untreated control, on fermentation, insilo losses, intake and performance of finishing cattle.In experiment 1, three covered concrete-walled silos were each filled with approximately 70 t of primary growth, unwilted herbage at each of two cutting dates, 20-21 May (early harvest) and 3 June 1985 (late harvest). In ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 5 publications
4
10
0
Order By: Relevance
“…The increase in N and organic matter digestibilities of the silages when offered alone, resulting from inoculant treatment, is in accordance with the results of other authors using sheep and dairy cattle (Hooper e/a/., 1984;Hooper etal.. 1987;Anderson et al, 1989;Gordon, 1989a), but Rooke et al (1988 and . using sheep and young cattle respectively, obtained no improvements in digestibility due to inoculant treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in N and organic matter digestibilities of the silages when offered alone, resulting from inoculant treatment, is in accordance with the results of other authors using sheep and dairy cattle (Hooper e/a/., 1984;Hooper etal.. 1987;Anderson et al, 1989;Gordon, 1989a), but Rooke et al (1988 and . using sheep and young cattle respectively, obtained no improvements in digestibility due to inoculant treatment.…”
Section: Discussionsupporting
confidence: 92%
“…whereas and Kennedy et al (1989) obtained poor fermentations in untreated silages using herbages with dry-matter concentrations of 165 and 168 g kg"' and water-soluble carbohydrate concentrations of 102 and 124 g (kg DM)'' respectively. The good feimentation reported here may be due to the rapid filling, air-tight sealing and the silo size (0 8 t capacity).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, formic acid treatment resulted in an increase in effluent output in line with data from a number of other studies (Norgaard-Pedersen, Moller and Skovberg, 1968;Kennedy, Gracey, Unsworth, Steen and Anderson, 1989). Pedersen, Olsen and Guttormsen (1973) suggested that the addition of formic acid to herbage at ensiling encourages a rapid release of soluble cell constituents as a result of changes in the lipophilic fraction of plant material.…”
Section: Composition Of Grass and Silage And In-silosupporting
confidence: 91%
“…Treatment of grass with inoculant had no effect on nutrient recovery after ensilage, in comparison with the overall mean recovery with the controls. Kennedy et al (1989) observed no effect of inoculant on recovery of DM. The tendency towards a higher recovery of energy with formic acid treat-ment reflects the findings of the review of Waldo (1977) that potential GE losses were reduced from 0·19 to 0·12 by the addition of formic acid to unwilted herbage.…”
Section: Silage Composition and In-silo Lossesmentioning
confidence: 78%